An amylase gene polymorphism is associated with growth differences in the Pacific cupped oyster Crassostrea gigas - Prudence, Marie; Moal, Jeanne; Boudry, Pierre; Daniel, Jean-yves; Quere, Claudie; Jeffroy, Fanny; Mingant, Christian; Ropert, Michel; Bedier, Edouard; Van Wormhoudt, A; Samain, Jean-francois; Huvet, Arnaud (Animal Genetics, 2006)
This study investigated the non-neutrality of genetic polymorphism in two alpha-amylase genes (AMYA and AMYB) in the oyster Crassostrea gigas. Bi-parental oyster families, bred to be polymorphic for markers in these genes, were monitored for growth and survival for 1 year under standard culture conditions in two French production sites. Within-family genotype frequencies indicated that the two amylase genes were closely linked (c. 1.7 cM). Within two of three families, significant differences in growth were observed between genotypes at one of the two production sites, suggesting that this polymorphism is not neutral and might be under selection because of its role in digestive function. Estimated daily yields were different between amylase genotypes, indicating the potential value of amylase markers in selective breeding programmes to improve oyster growth.